ANALISIS MAKNA TINDAK TUTUR ILOKUSI MAHASISWA PBSI ANGKATAN 2022 FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS NUSA CENDANA - Fransiska Meldiana Gimur; Karolus Budiman Jama; Aris Nurhuda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is entitled “An Analysis of the Meaning of Illocutionary Speech Acts of PBSI Students of the 2022 Cohort, Faculty of Teacher Training and Education, Universitas Nusa Cendana.” The problem investigated in this study is the meaning of illocutionary speech acts. The objective of this study is to describe the meanings of illocutionary speech acts used by PBSI students of the 2022 cohort in the Faculty of Teacher Training and Education, Universitas Nusa Cendana. The method employed in this study is a descriptive qualitative approach. The data were collected using the observation and note-taking technique, by carefully listening to the utterances produced by both speakers and their interlocutors. The theoretical framework applied in this study is Searle’s speech act theory. Based on the findings, there are five types of illocutionary speech acts identified: (1) assertive, (2) directive, (3) expressive, (4) commissive, and (5) declarative. Furthermore, the analysis reveals six meanings in the conversations of PBSI students of the 2022 cohort in the Faculty of Teacher Training and Education, Universitas Nusa Cendana: (1) assertive suggesting, (2) assertive complaining, (3) directive requesting, (4) expressive apologizing, (5) commissive promising, and (6) declarative resignation.